William Shakespeare - Dickens, Rosie (b, 2008)
William dreams of acting and writing plays. This ambition takes him from the quiet country town of Stratford, where he grows up, to the great playhouses of London. His talent takes the city by storm. But how will he cope with jealous rivals, strict censorship, plague and plotting earls?